“Beyond the Standard Model: where do we go from here?” - AAVV, AAVV (Il Colle di Galileo, 2019)
The workshop brought together a large number of theorists and experimentalists from a variety of areas of physics, with a majority from high energy particle physics and a significant fraction from low energy, atomic, molecular and optics, as well as accelerator physics. The topics discussed ranged across a wide field of future experimental investigations of physics beyond the Standard Model, both with low and high energy probes, including a focus on future accelerator facilities currently under discussion worldwide. The workshop enjoyed the presence of Simons Fellows, who led broad-scope discussions on the directions of future research in the exploration of physics beyond the Standard Model.